Validation of Diagnoses of Atopic Dermatitis in Hospital Registries: A Cross-sectional Database Study from Finland - Miika Kurki; Suvi-Päivikki Sinikumpu; Eetu Kiviniemi; Jari Jokelainen; Laura Huilaja (Acta Dermato-Venereologica, 2023)
Abstract is missing (Short communication)